Antibiotic Profile of Extended Spectrum Beta Lactamase Escherichia coli from Clinical Samples - Chaudhary, Mahesh Kumar; Jadhav, Indrani; Jadhav, Indrani; Banjara, Megha Raj (Journal of Karnali Academy of Health Sciences, 2020)
Background: Extended spectrum β-lactamases have addressed the serious challenges worldwide due to the emergence of ESBL producing genes which possess a serious threat for the treatment of infections both in community and hospitals since it is found to be increasing trends of multidrug resistance. This study was focused to find out the antibiotic profile of multidrug resistant Escherichia .coli and status of ESBLs producing E.coli. Methods: This was a cross-sectional study conducted over a period of 2 years (September 2017 to April 2019) at microbiology laboratory of Nepal Mediciti Hospital. A total of 16542 samples were processed. Various clinical samples were collected from both inpatients and outpatients aseptically and without contaminating skin commensals. Standard microbiological techniques were used for isolation and identification of pathogens. Extended spectrum beta-lactamases were phenotypically confirmed by combined disc method. Results: Out of 1449 E.coli isolates, 323(22.29%) were found to be MDR E.coli. Isolation rate of ESBL producing E.coli (66.56%) were found to be high among MDR E.coli isolates. Conclusion: There was increasing prevalence of ESBL producing E.coli and was essential to monitor antibiotic susceptibility pattern and formulate antibiotic policy to prevent the spread of MDR and ESBL producers.